Design and experimental evaluation of a tilt-angle propeller test rig for vertical thrust characterisation of the TRQ-1 quadcopter - Ismail, Noor Iswadi; Basri, M. Hisyam; Amir, Muhammad Amirul Hakim; Ab Hamid Pahmi, Muhammad Arif; Rabilah, Rosniza; Mohammud, Mohd Mahadzir (Smart Manufacturing Research Institute (SMRI), 2025)
This study presents the design and experimental evaluation of a custom-built test rig that was specially developed for vertical thrust measurement of the TRQ-1 quadcopter prototype, The test rig was designed to replicate the TRQ-1's tilt mechanism. The custom-built test rig enables accurate and repeatable thrust measurements under varying tilt-angles. In this work, a series of experiments were conducted using an APC 10×5 propeller to quantify vertical thrust at 0°, +15°, and -15° tilt-angles across a range of rotational speeds starting from 1500 RPM up to a maximum of 5500 RPM. Validation against available manufacturer thrust data confirmed the rig's measurement accuracy, and deviations from manufacturer thrust data were generally within ±5%, with a maximum deviation of 7.12% at low RPM (2010) and minimum deviation of 1.33% at higher RPM (3060–5010). These values confirmed the accuracy of the rig within acceptable engineering tolerances. The results indicated that a +15° forward tilt configuration consistently reduces vertical thrust due to thrust vector redirection. Meanwhile, the -15° rearward tilt configuration yielded a modest increase in vertical thrust, especially at lower RPMs range. These findings are consistent with aerodynamic theory, which highlights the trade-off between thrust vectoring for manoeuvrability and vertical lift performance. The proposed test rig demonstrates reliable performance and provides a consistent tool to evaluate the aerodynamic behaviour of tilt-propeller quadcopter configurations.